Systematic Review: Leadership Style in Maintaining Business Sustainability in the MSME Industry - Aristayudha, A A Ngurah Bagus; Riana, I Gede; Rahyuda, Agoes Ganesha; Surya, Ida Bagus Ketut (Global Health Science Group, 2023)
Leadership style is the way a leader chooses to direct or coordinate the work that will be given to his subordinates. The leadership style chosen by a leader depends on the goals of the organization or company, who is being led, and the type of business led by the leader. Systematic review using the Google Scholar database. Search results using the keyword leadership style in maintaining business continuity in the MSME industry